Evaluasi Pengalaman Penggunaan Aplikasi Onklas Pada SMAN 11 Surabaya Meggunakan Metode User Experience Questionnaire (UEQ) - Noer Alam Yahya (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2024)
The rapid development of Information and Communication Technology (ICT) has had a significant impact over time. Technological advancements in recent years have enabled the creation of more effective efforts and enriched the learning environment. User experience is described as the experience gained by users when using software products. This research aims to understand the experience obtained by users when using the Onklas application system. Measurement is conducted using the User Experience Questionnaire (UEQ). The study was conducted at SMAN 11 Surabaya with 290 respondents who are students of the school. This thesis evaluates the use of the Onklas The assessment of the application utilized the User Experience Questionnaire (UEQ). The UEQ methodology comprises 26 questionnaire items, serving as instruments categorized into 6 scales: attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. The study encompassed a population of 290 respondents, selected through the Slovin sampling technique. The outcomes of the user experience evaluation employing UEQ for each aspect are as follows: attractiveness 1.305, perspicuity 1.186, efficiency 1.214, dependability 1.200, stimulation 1.251, and novelty 1.246. These findings indicate that all facets of the user experience have been assessed. received positive impressions.